2013
DOI: 10.1002/ejic.201300746
|View full text |Cite
|
Sign up to set email alerts
|

Why Does the Coordination Mode of Physiological Bis(L‐histidinato)copper(II) Differ in the Gas Phase, Crystal Lattice, and Aqueous Solutions? A Quantum Chemical Study

Abstract: In bis(L‐histidinato)copper(II), the amino acid L‐histidine can bind to copper(II) in glycine‐like (G), histamine‐like (H), and imidazole–propionic acid like (I) coordination modes. This complex is known as the predominant copper(II)–amino acid complex in human blood serum. Numerous experimental studies of this physiological complex reported several coordination modes to coexist in aqueous solutions, but without providing complete structures. This paper is the first to investigate the relative stability of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 55 publications
3
5
0
Order By: Relevance
“…The nonrelativistic effective-core potentials (ECPs) of Hay and Wadt (LanL2DZ) were used to describe the shielding effects of electrons in copper inner shells. This basis set will be named BS0 in the following. The choice of this combination of density functional and basis set was based on previous studies of anhydrous and aqua Cu­(aa) 2 complexes, in which the DFT/B3LYP results were verified against experimental X-ray crystal and molecular structures. ,, Besides, the energetics calculated by B3LYP/BS0 for the stationary points of bis­(glycinato)­copper­(II) (Cu­(Gly) 2 ) matched well with the corresponding energy values obtained with G3 calculations at the MP2 level …”
Section: Theoretical Calculationssupporting
confidence: 56%
See 2 more Smart Citations
“…The nonrelativistic effective-core potentials (ECPs) of Hay and Wadt (LanL2DZ) were used to describe the shielding effects of electrons in copper inner shells. This basis set will be named BS0 in the following. The choice of this combination of density functional and basis set was based on previous studies of anhydrous and aqua Cu­(aa) 2 complexes, in which the DFT/B3LYP results were verified against experimental X-ray crystal and molecular structures. ,, Besides, the energetics calculated by B3LYP/BS0 for the stationary points of bis­(glycinato)­copper­(II) (Cu­(Gly) 2 ) matched well with the corresponding energy values obtained with G3 calculations at the MP2 level …”
Section: Theoretical Calculationssupporting
confidence: 56%
“…Knowledge of isolated complex conformers is a prerequisite to examine and rationalize the influence of intermolecular interactions on the overall complex geometry and the coordination modes in the crystal lattice and aqueous solutions. Another motivation was to do a follow-up study of our previous work on physiological bis­( l- histidinato)­copper­(II), which examined the relative stability of all possible copper­(II) coordination modes and conformations of that complex in the gas phase, and several conformers surrounded with 2, 8, 10, 20, and 22 water molecules by DFT/B3LYP calculations . We concluded that the intermolecular interactions and the arrangement of water molecules around the complex might affect different coordination mode formation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, solvent of 50:50 water/methanol (0.1% formic acid) was crucial for the detection of protonated complexes and potassium adduct complexes. Among the chiral selectors investigated, the copper-bound diastereomers [Cu­(II)­(naproxen)­(His)−H] + ( 12 ) and [(Cu­(II)) 2 (naproxen)­(His) 2 −3H] + ( 13 ) (Figure S1) were observed only with His as the chiral selector, which was likely because of the coordination site provided by the imidazole ring in the side chain of histidine in addition to its amino and carboxylic groups. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…Among the chiral selectors investigated, the copper-bound diastereomers [Cu(II)-(naproxen)(His)−H] + (12) and [(Cu(II)) 2 (naproxen)-(His) 2 −3H] + (13) (Figure S1) were observed only with His as the chiral selector, which was likely because of the coordination site provided by the imidazole ring in the side chain of histidine in addition to its amino and carboxylic groups. 45,46 Figure S2 shows the CID spectra of some typical naproxencontaining diastereomeric complex ions, including (a) [naprox-en+2γ-CD+2H] + ( 2 (15). For all except the copper-containing complexes, loss of naproxen was observed.…”
Section: ■ Results and Discussionmentioning
confidence: 99%